Bioaccumulation of polystyrene nanoplastics and their effect on the toxicity of Au ions in zebrafish embryos. Issue 7 (10th December 2018) - Lee, Wang Sik; Cho, Hyun-Ju; Kim, Eungwang; Huh, Yang Hoon; Kim, Hyo-Jeong; Kim, Bongsoo; Kang, Taejoon; Lee, Jeong-Soo; Jeong, Jinyoung
Abstract : Size- and dose-dependent bioaccumulation of polystyrene nanoplastics influence on the toxicity of gold ion in zebrafish embryos. Abstract : As nano- and micro-sized plastics accumulate in the environment and the food chain of animals, including humans, it is imperative to assess the effects of nanoplastics in living organisms in a systematic manner, especially because of their ability to adsorb potential toxicants such as pollutants, heavy metals, and organic macromolecules that coexist in the environment. Using the zebrafish embryo as an animal model, we investigated the bioaccumulation and in vivo toxicity of polystyrene (PS) nanoplastics individually or in combination with the Au ion. We showed that smaller PS nanoplastics readily penetrated the chorion and developing embryos and accumulated throughout the whole body, mostly in lipid-rich regions such as in yolk lipids. We also showed that PS nanoplastics induced only marginal effects on the survival, hatching rate, developmental abnormalities, and cell death of zebrafish embryos but that these effects were synergistically exacerbated by the Au ion in a dose- and size-dependent manner. Such exacerbation of toxicity was well correlated with the production of reactive oxygen species and the pro-inflammatory responses synergized by the presence of PS, supporting the combined toxicity of PS and Au ions. The synergistic effect of PS on toxicity appeared to relate to mitochondrial damage as determined by ultrastructural analysis. Taken together, the effects of PS nanoplastics were marginal but could be a trigger for exacerbating the toxicity induced by other toxicants such as metal ions.